Improving immunological tumor microenvironment using electro-hyperthermia followed by dendritic cell immunotherapy. Issue 1 (December 2015) - Tsang, Yuk-Wah; Huang, Cheng-Chung; Yang, Kai-Lin; Chi, Mau-Shin; Chiang, Hsin-Chien; Wang, Yu-Shan; Andocs, Gabor; Szasz, Andras; Li, Wen-Tyng; Chi, Kwan-Hwa
Abstract Background The treatment of intratumoral dentritic cells (DCs) commonly fails because it cannot evoke immunity in a poor tumor microenvironment (TME). Modulated electro-hyperthermia (mEHT, trade-name: oncothermia) represents a significant technological advancement in the hyperthermia field, allowing the autofocusing of electromagnetic power on a cell membrane to generate massive apoptosis. This approach turns local immunogenic cancer cell death (apoptosis) into a systemic anti-tumor immune response and may be implemented by treatment with intratumoral DCs. Methods The CT26 murine colorectal cancer model was used in this investigation. The inhibition of growth of the tumor and the systemic anti-tumor immune response were measured. The tumor was heated to a core temperature of 42 °C for 30 min. The matured synergetic DCs were intratumorally injected 24 h following mEHT was applied. Results mEHT induced significant apoptosis and enhanced the release of heat shock protein70 (Hsp70) in CT26 tumors. Treatment with mEHT-DCs significantly inhibited CT26 tumor growth, relative to DCs alone or mEHT alone. The secondary tumor protection effect upon rechallenging was observed in mice that were treated with mEHT-DCs. Immunohistochemical staining of CD45 and F4/80 revealed that mEHT-DC treatment increased the number of leukocytes and macrophages. Most interestingly, mEHT also induced infiltrations of eosinophil, which has recently been reported to be an orchestrator of a specific T cell response. Cytotoxic T cell assay and ELISpot assay revealed a tumor-specific T cell activity. Conclusions This study demonstrated that mEHT induces tumor cell apoptosis and enhances the release of Hsp70 from heated tumor cells, unlike conventional hyperthermia. mEHT can create a favorable tumor microenvironment for an immunological chain reaction that improves the success rate of intratumoral DC immunotherapy.